2019
DOI: 10.1111/basr.12168
|View full text |Cite
|
Sign up to set email alerts
|

Assessing UNGC pharmaceutical signatories stakeholders using big data

Abstract: This article aims to focus on how signatories versus nonsignatories in the U.S. pharmaceutical sector compare with respect to the internal and external stakeholders and principles of the United Nations Global Compact (UNGC). We seek to answer the question: Do signatories to the UNGC walk the talk better than nonsignatories as determined by a variety of published rankings and data? This research presents an innovative approach to the evaluation of UNGC signatories. It uses several objective and independent data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Thus, incorporating SDGs for reputational reasons cannot be rejected. This fully corresponds with the previous criticism of the implementation gap (Fortín and Jolly 2015;Pingeot 2015), and, in particular, the insufficiencies of COPs themselves (Coulmont et al 2017;Zilic et al 2019). Nevertheless, findings presented in this study go further, indicating that the expectations related to the importance of the UNGC for the implementation of the SDGs by 2030 might be strongly exaggerated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, incorporating SDGs for reputational reasons cannot be rejected. This fully corresponds with the previous criticism of the implementation gap (Fortín and Jolly 2015;Pingeot 2015), and, in particular, the insufficiencies of COPs themselves (Coulmont et al 2017;Zilic et al 2019). Nevertheless, findings presented in this study go further, indicating that the expectations related to the importance of the UNGC for the implementation of the SDGs by 2030 might be strongly exaggerated.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, regarding the UNGC, the research so far has identified many problems, in particular, substantial cross-country differences in adoption and disclosure levels (Ali and Frynas 2018;Schembera 2018;Lim 2017); insufficient quality of annual Communications on Progress (COPs), the primary tool for monitoring participants' commitment to the UNGC Ten Principles (Coulmont et al 2017;Zilic et al 2019); as well as numerous cases of companies adhering to the Principles for the instrumental reasons of seeking protection from criticism and improving their reputation rather than having real intentions of applying them in their everyday operations (Amer 2018;Wettstein et al 2019). Moreover, studies on the practical impacts of the UNGC on the business operations and risk management of companies are almost non-existent (cf.…”
Section: Literature Review and The Rationale Of The Studymentioning
confidence: 99%
See 1 more Smart Citation